FUNGI OCCURRED ON TURFGRASSES IN LAWN MAINTENANCE - Irena Kiecana; Małgorzata Cegiełko; Elżbieta Mielniczuk (Acta Scientiarum Polonorum: Hortorum Cultus, 2015)
In recent years there has been an increasing interest in lawns and their appearance. Diseases affecting lawns, of which the causative agents can be various pathogens, reduce their quality. The study was conducted in two urban centers in the region of southeastern Poland – in the years 2006 and 2007 in Lublin and in 2007 in Zamość, both in sunny and in partly shaded places. The species composition of the grass sward and the severity of leaf infection were determined as well as mycological analysis of infected plants was carried out. In the case of the lawns in Lublin, the mean values of the disease indices for the leaves of the investigated turfgrasses were from 53.75 to 83.00 in the spring of 2006, while in spring of 2007 from 6.75 to 29.00. The mean values of the leaf disease indices determined in autumn of 2006 were from 16.00 to 86.25, whereas in autumn of 2007 from 4.50 to 21.25. The mean values of the disease indices for leaves of the turfgrasses studied in Zamość were from 24.50 to 48.25 in the spring of 2007, while in the autumn of that year they ranged from 28.00 to 54.75. Microdochium nivale was a great threat to turfgrasses in lawn culture in spring, whereas the cause of leaf spot of turfgrasses in the autumn were species B. sorokiniana and D. siccans. As far as the lawns in both cities are concerned, species of the genus Fusarium, in particular Fusarium culmorum, had a high percentage in root infection both in the spring and in the autumn.